ROOT CAUSE ANALYSIS FOR CONDUCTING UNIVERSITY’S COMMUNITY SERVICE TO MICRO AND SMALL FIRMS - Sri Maryanti; Afred Suci; Nining Sudiar; Hardi Hardi (Jurnal Manajemen dan Kewirausahaan, 2020)
The study aims to identify the root problems facing by the small firm that further can guide the university to implement the most appropriate treatments to enhance the partnering small firm's business performance. A qualitative approach was employed, primarily conducting in-depth interviews and brainstorming with business owners, employees, store managers, and consumers of "Wajik Tapai" in Riau Province, in the framework of root cause analysis. The result reveals that the distinct causes identified as the driver of the small firm's income stagnation can be rooted in four perspectives, i.e., product durability, non-ergonomic working layout with a traditional process, conventional/offline marketing, and variability of product.